Effect Of Ramadhan Fasting On Apolipoprotein B And Small Dense Ldl In Type 2 Diabetes Mellitus Patients - Joseph Partogi Sibarani (International Journal of Health and Pharmaceutical (IJHP), 2024)
This study's objective was to ascertain how type 2 Diabetes Mellitus patients' apolipoprotein B and small dense LDL were affected by Ramadan fasting. On 19 patients who had been diagnosed with type 2 DM at H. Adam Malik General Hospital Medan, a longitudinal prospective study from the fasting month of Ramadan until the end of the 2015 Ramadan fast was employed as the research methodology. The information was gathered by obtaining blood samples at the start and end of the Ramadan fast, after which the levels of apolipoprotein B and small dense LDL were determined. The T-Test and Wilcoxon tests were then used to assess the data. According to the study's findings, 13 respondents (68.4%) of the 19 patients with type 2 diabetes were men, and their average age was 57.26 years. Apoliprotein B (p=0.0001), small dense LDL (p=0.022), 2-hour PPG DGD (p=0.039), and mean body weight (p0.001) all indicated statistically significant changes. According to the study's findings, type 2 DM patients' apolipoprotein B and small dense LDL are significantly affected by Ramadan fasting.